Web application for staff selection through diffuse evaluations intervals - Estrada Esponda, Royer David (Scientia et Technica, 2018)
In most companies, staff selection processes are highly relevant due the constant employers’ need to have a qualified and trained human resource to meet the organizational challenges. This article presents the Web application resulting from the degree project called "Web Recommendation System for Selecting Personnel Based on Software Agents", with the purpose of serving as a reference for works oriented to improve personnel selection processes in organizations.